CAUSES OF CHILDREN’S MORTALITY (REVIEW) - D. V. Prometnoy; E. A. Spiridonova; S. A. Rumiantsev; F. G. Sharshov (Медицинский вестник Юга России, 2013)
The leading causes of children’s mortality in the world, Europe and Russian Federation and the ways of decreasing of quantity of lethal outcomes were researched. The role of healthcare system in prevention of mortality causes among the children and adolescents is discussed.